PENERAPAN METODE BERNYANYI DALAM MENINGKATKAN PENGUASAAN MUFRADAT DALAM PEMBELAJARAN BAHASA ARAB DI RAODHATUL ATHFAL - Ridwan Ridwan; A. Fajar Awaluddin (Didaktika : Jurnal Kependidikan, 2019)
This study aims to improve the acquisition of Arabic vocabulary in early childhood with singing techniques. Children of all ages are basically happy to listen, sing and learn with songs. Therefore, music in general is an important part of the teaching-learning process for young students. The results showed that early childhood students enjoyed learning Arabic by singing and it was easier to remember the vocabulary taught by the teacher. Thus, it can be concluded that  the singing technique is able to improve the mastery of early childhood Arabic vocabulary especially for students of the Raodhatul Athfal Ma'had Hadits Al-Junaidiyah Blue Bone.Keywords: Singing technique, vocabulary mastery, Arabic